Platelet-rich plasma products in sports medicine - Bava, E. D.; Barber, F. A. (The Physician and Sportsmedicine, 2011)
Platelet-rich plasma (PRP) therapy is a recently developed technique that uses a concentrated portion of autologous blood to try to improve and accelerate the healing of various tissues. There is considerable interest in using these PRP products for the treatment of musculoskeletal disorders, particularly athletic injuries. Because PRP products are safe and easy to prepare and administer, there has been increased attention toward using PRP in numerous clinical settings. Platelet-rich plasma has been used to treat conditions such as lateral epicondylitis, ligament and muscle strains, and tears of the rotator cuff, anterior cruciate ligament, and Achilles tendon. Platelet-rich plasma can be applied at the site of injury either during surgery or through an injection performed in the physician`s office. The benefits of PRP therapy appear to be promising, and many investigators are exploring the ways in which this therapy can be used in the clinical setting. However, there is little published clinical evidence that proves its efficacy in treating the multitude of injuries/disorders that are thought to benefit from PRP. The purpose of this article is to review the current evidence on PRP therapy.